In vivo role of capsular polysaccharide in Mycoplasma mycoides - Jores, Joerg; Schieck, Elise G.; Liljander, Anne M.; Sacchini, Flavio; Posthaus, H.; Lartigue, C.; Blanchard, Alain; Labroussaa, F.; Vashee, S. (Oxford University Press, 2019)
Capsular polysaccharides have been confirmed to be an important virulence trait in many gram-positive and gram-negative bacteria. Similarly, they are proposed to be virulence traits in minimal Mycoplasma that cause disease in humans and animals. In the current study, goats were infected with the caprine pathogen Mycoplasma mycoides subsp. capri or an engineered mutant lacking the capsular polysaccharide, galactofuranose. Goats infected with the mutant strain showed only transient fever. In contrast, 5 of 8 goats infected with the parental strain reached end-point criteria after infection. These findings confirm that galactofuranose is a virulence factor in M. mycoides.